The firm under uncertainty: capital structure and background risk - Udo Broll; Keith K.P. Wong (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2010)
This paper examines the interplay between the real and financial decisions of the competitive firm under output price uncertainty. The firm faces additional sources of uncertainty that are aggregated into a background risk. We show that the firm always chooses its optimal debt-equity ratio to minimize the weighted average cost of capital, irrespective of the risk attitude of the firm and the incidence of the underlying uncertainty. We further show that the firm's optimal input mix depends on its optimal debt-equity ratio, thereby rendering the interdependence of the real and financial decisions of the firm. When the background risk is either additive or multiplicative, we provide reasonable restrictions on the firm's preferences so as to ensure that the firm's optimal output is adversely affected upon the introduction of the background risk.
Keywords: D21; D81; G32; 330; Background risk; Capital structure; Price uncertainty; Kapitalstruktur; Entscheidung bei Unsicherheit; Finanzierungstheorie; Preis; Risiko; Theorie